(untitled) (GEON Journal (Management, Organizations and Business), 2015)
In the framework of the implementation of social marketing as a tool to influence the voluntary behavior of target audiences in order to improve their personal welfare and community , the research process conducted by the (as) students documented seed marketing " marketers in Action" where a diagnosis , implementation of training and creating a marketing plan for the development of a sustainable viable project with groups of entrepreneurs and traders verada Candelaria Township Ráquira , Boyacá Department developed.